The Wizard of Oz [Čarodejník z krajiny Oz anglicky] - Baum, Lyman Frank, 1856-1919 (Best of children´s classics, 2022)
Dorothy and her canine pal Toto live a quiet life on a Kansas farm with Uncle Henry and Aunt Em. But one day, the little girl and her dog find themselves spirited away from the fields of Kansas, to the magical land of Oz! Dorothy and Toto meet many friends on the yellow-brick road to Emerald City, where she hopes to find a way home to Kansas-- but when she arrives, the city's mysterious ruler, the Wizard of Oz, is not what she expects!